Environmental evolution in Sierra Nevada (South Spain) since the Last Glaciation, based on multi-proxy records - Oliva, Marc (2014)
Our knowledge of the Quaternary landscape evolution in the high mountain areas of the Iberian Peninsula has substantially improved over the last decades. The Sierra Nevada is one of the most studied mountain ranges in southern Europe regarding its environmental evolution. The purpose of the present paper is to integrate and summarize all the studies focused on the reconstruction of the palaeoenvironmental history in this massif since the Last Glaciation. Research has focused both on different sedimentary records and historical sources. A wide range of geomorphological, sedimentological and geochronological techniques have been used to characterize the glacial, periglacial, wetland and lacustrine records for palaeoenvironmental purposes. For the last nine centuries tens of descriptions, maps and sketches describe the landscape of the summit area of the Sierra Nevada, providing evidences of the historical environmental events. Based on a multi-proxy approach, five periods have been identified: Last Glaciation, deglaciation, Holocene, Little Ice Age and recent evolution. Recent studies have detected the maximum expansion of glaciers in the Sierra Nevada around 30–32 ka BP, predating the global temperature minimum. No data about the environmental evolution is available between 20–30 ka BP. Around 19–20 ka BP glaciers advanced significantly. The process of deglaciation was rapid and around 14–15 ka BP the massif was almost free of ice. The Late Glacial promoted the formation of small glaciers in the highest northern cirques and widespread active periglacial processes (i.e. rock glaciers). During the Holocene there has been an alternation of colder/warmer periods and changing moisture conditions. Periglacial processes have been generally widespread in the summit area, with an increasing or decreasing activity depending on climate conditions. Ephemeral reappearance of small glacial cirques occurred in the highest northern cirques during the coldest and wettest phases. This is the case of the Little Ice Age, as revealed by historical documents and sedimentary records. Since the last decades of the XIX century the temperature has increased ∼0.93°C leading to a decrease of the intensity of periglacial processes in the high lands of the Sierra Nevada.